2017
DOI: 10.18632/oncotarget.17894
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma histological subtype distribution differs by age, gender, and tumor size in coastal Chinese patients

Abstract: The distribution pattern of renal cell carcinoma (RCC) histological subtypes according to age, gender and tumor size has not been well illustrated in RCC patients living in fast-developing regions of China. We recruited 2941 patients with clear cell renal cell carcinoma (ccRCC), papillary renal cell carcinoma (PCC) or chromophobe from two hospitals in coastal China (2004−2012) consecutively and draw 538 American Chinese RCC patients’ data with time matched from the Surveillance, Epidemiology, and End Results d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…Clear cell renal cell carcinoma (ccRCC), as the most common histological type of RCC, accounts for approximately 85% of all primary renal neoplasms [ 2 ]. The overall 5-year survival rate of RCC is 74% and 16% of patients have been diagnosed with local invasion or distant metastasis, resulting in a poorer prognosis [ 3 ]. Hence, the early diagnosis and treatment of ccRCC are imperative and challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Clear cell renal cell carcinoma (ccRCC), as the most common histological type of RCC, accounts for approximately 85% of all primary renal neoplasms [ 2 ]. The overall 5-year survival rate of RCC is 74% and 16% of patients have been diagnosed with local invasion or distant metastasis, resulting in a poorer prognosis [ 3 ]. Hence, the early diagnosis and treatment of ccRCC are imperative and challenging.…”
Section: Introductionmentioning
confidence: 99%
“…However, some researchers have reported that other clinicopathological factors such as race, sex, age, tumor size, and mode of presentation may also influence the RCC patients’ outcomes. 13 15 No single factor can account for the wide variability of outcomes observed in individual patients. Neglecting these significantly prognostic parameters may reduce the accuracy of survival predictions.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Recently, 90.7% of RCC had been ccRCC, which was reported in a Chinese study. 4 Progression has been made to manage the patients for different diagnoses and treatments of ccRCC. Cancer metastasis and invasion lead to 90% of patient deaths, and ~30% of patients have been diagnosed with local invasion or distant metastasis, resulting in a poor prognosis.…”
Section: Introductionmentioning
confidence: 99%